Toxicological and morphological effects of tebufenozide on Anticarsia gemmatalis (Lepidoptera: Noctuidae) larvae. (December 2018) - Fiaz, Muhammad; Martínez, Luis Carlos; Plata-Rueda, Angelica; Gonçalves, Wagner Gonzaga; Shareef, Muhammad; Zanuncio, José Cola; Serrão, José Eduardo
Abstract: The velvetbean caterpillar, Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae), is an important soybean pest in the Americas. Tebufenozide, a novel nonsteroidal ecdysone agonist is used to control this pest. Bioassays were conducted to assess tebufenozide toxicity and their ultrastructural effects on midgut of A. gemmatalis . The toxicity, survivorship, behavior response, and respiration rate for A. gemmatalis larvae after exposure to tebufenozide were evaluated. Also, A. gemmatalis larvae were treated with LC50 obtained from tebufenozide and changes were observed on their midgut cells after 24, 48 and 96 h. Tebufenozide was toxic to A. gemmatalis (LC50 = 3.86 mg mL −1 and LC90 = 12.16 mg mL −1 ) and survivorship was 95% for adults that had not been exposed to tebufenozide, decreasing to 52% with LC50 and 27% with LC90 estimated value. Damage to midgut cells was increased with exposure time. These cells show damaged striated border with release of protrusions to the midgut lumen, damaged nuclear membrane and nucleus with condensed chromatin and increase in amount of autophagic vacuoles. Mitochondria were modified into nanotunnels which might be an evidence that tebufenozide induces damage to cells, resulting in cell death, proved by immunofluorescence analyses. This insecticide also caused paralysis movement with change in homeostasis and compromised larval respiration. Thus, sublethal exposure to tebufenozide is sufficient to disturb the ultrastructure of A. gemmatalis midgut, which might compromise insect fitness, confirming tebufenozide a possible controlling insecticide. Highlights: The insecticidal effect of Tebufenozide was tested against A. gemmatalis. A. gemmatalis showed significant changes in histology and ultrastructure. Induction of mitochondrial nanotunnels by Tebufenozide. Tebufenozide compromises respiration and behavior of A. gemmatalis.